Case series on anti-melanoma differentiation-associated gene 5+ dermatomyositis associated with interstitial lung disease - Pranathiya, Koya; Anusha, Are; Sam, Kezia; Manda, Anusha (International Journal of Basic & Clinical Pharmacology, 2023)
Dermatomyositis (DM) associated with anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody is a rare autoimmune disease. Anti-MDA5, also known as anti-CADM-140 antibodies. DM affects the skeletal muscle, skin, joints, and lungs and is a form of idiopathic inflammatory myopathy (IIM). All the 5 dermatomyositis MDA5+ positive patients had rapidly progressive interstitial lung disease (RP-ILD). DM is classified into 2 types, classic dermatomyositis (CDM) and clinically amyopathic dermatomyositis (CADM). Anti-MDA5 antibody-positive as RP-ILD without signs of DM or CADM. RP-ILD in patients with CADM associated with antibodies to MDA5 has a high mortality rate. MDA5+ DM is diagnosed by DM rashes (Gottron’s papules or Gottron’s sign and heliotrope rash) and a positive anti-MDA5. RP-ILD includes acute/subacute interstitial pneumonia, which is a progressive deterioration associated with ILD. Immunosuppressives are effective agents for the treatment of anti-MDA5-positive RP-ILD of CADM.